Decoupled and Memory-Reinforced Networks: Towards Effective Feature Learning for One-Step Person Search - Han, Chuchu (ASSOC ADVANCEMENT ARTIFICIAL INTELLIGENCE, 2023)
35th AAAI Conference on Artificial Intelligence / 33rd Conference on Innovative Applications of Artificial Intelligence / 11th Symposium on Educational Advances in Artificial Intelligence